Teachers’ Perceptions toward Teaching English in Mixed- Ability classrooms at the Secondary Level of Education in Bangladesh - Thaniyatul Jannath, Samira; Naiem, Al Amin; Khan Sarfaraz, Ali; Ida, Hindarsah (INTI International University, 2025)
This article reports on a qualitative study examining secondary school teachers’ attitudes and perceptions toward teaching English in mixed-ability classrooms in Dhaka, Bangladesh. The study’s primary objective was to identify the challenges English teachers face when instructing students with varying levels of proficiency and to propose strategies for more inclusive and effective teaching practices. Data was collected through semi-structured interviews and classroom observations. Ten English language teachers five from each of two secondary schools were interviewed using open-ended questions, and six classroom observations were conducted, each involving approximately fifty students. The observations aimed to explore teachers’ psychological attributes, tolerance, and adaptive strategies in managing diverse learning needs, as well as patterns of student participation. Thematic analysis revealed key challenges related to differentiated instruction, classroom management, and assessment fairness. However, teachers also demonstrated creativity and resilience in employing learner-centered techniques to foster inclusion. Aligned with SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), this study highlights the importance of supporting teachers through professional development and policy initiatives that promote inclusive pedagogies and equitable access to English language learning in mixed-ability classrooms